PENGEMBANGAN BAHAN AJAR MATEMATIKA TEKNIK BERBASIS PEMBELAJARAN PROYEK BERBANTUAN KOMPUTER UNTUK MENINGKATKAN KEMAMPUAN PENALARAN DAN KOMUNIKASI MATEMATIKA MAHASISWA - Wasiran, Yulianto; Maja, Ibnu; Lindawati, Lindawati; Husin, Farida (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA, 2017)
This study aimed at producing appropriate Computer Assisted Mathematics Based Project (valid, practical, and effective) teaching materials to improve students reasoning and mathematical communication skills. This research is a development research, which develops teaching materials using 4-D models. The instruments of data collection used are validation of teaching materials, questionnaires, and tests of reasoning ability and mathematical communication. Based on the results of data analysis up to stage 3 on R & D research revealed that the compiled teaching materials have met the eligibility requirements. Feasibility level of teaching materials equal to 85.58% with high category. The result of the test of teaching material is 88,4. This means that the teaching materials have excellent value with a high level of practicability. The effectiveness test shows that there is a significant difference between the pre-test and post-test values. In relation to the assessment of the conformity of teaching materials content with the project-based learning stage, 83.3% of respondents agreed that the material in textbooks put forward the project and the evaluation used could represent the problem solving in the real world. All respondents agree that by learning through developed learning materials, learners are encouraged to design their own products to be done. All respondents agree that from the project assigned, learners are encouraged to develop their competence.